Effect of post weld heat treatment on metallurgical and mechanical properties of electron beam welded AISI 409 ferritic steel - Doomra, Akash; Sandhu, Sandeep Singh; Singh, Beant (Metallurgical and Materials Engineering, 2020)
The applicability of ferritic stainless steel is restricted due to its low weldability, and this can be attributed to the severe grain growth in the weld zone during the solidification of the weld pool and formation of fully ferritic structure. This study aims to investigate the weldability of 18 mm thick AISI 409 ferritic stainless steel plates using an electron beam welding process without the use of filler metal. The joints were investigated for metallography characterization (microstructure, macrostructure, and microhardness) and mechanical behavior (tensile strength and impact toughness) in as-welded condition and after post-weld heat treatment at 550 ºC for 75 minutes. The weld zone exhibited large columnar grains in the direction perpendicular to the weld centerline and got refined after post-weld heat treatment. The ultimate tensile strength, yield strength, and microhardness of the weld zone were found higher than the base metal. The impact toughness of weld zone was found to be reduced by 45%, but the post-weld heat treatment improved the toughness by 40%. Results revealed that the electron beam welding process could be successfully employed for welding of AISI 409 ferritic stainless steel, which will increase its application range that requires thicker section of welded plates. Post-weld heat treatment was found to be advantageous for improving the microstructure and mechanical properties.